MEASURING THE TAX CHARGE INCIDENTS ON NATIONAL WINE: IMPACT ON THE COMPETITIVENESS OF BIO-INDUSTRIE - Farinon, Kemylli; Gelinski Junior, Eduardo; Rogoski, Nédio Ricardo; de Barros, José Eduardo (Anais eletrônicos do International Symposium on Science and Biotechnology, 2017)
The increase in the national tax burden on wine production in heading 2204 of the Tax Incidence Table on Industrialized Products-TIPI, which is the object of this study, is one of the factors of economic loss and competitiveness for small and medium-sized bio-industries. The objective is to evaluate the preventive act, according to the Brazilian legislation, which allows to pay the smallest possible amount of taxes, in order to verify the lower tax burden. It is qualitative, descriptive and analytical research. Viti-winemakers are included in the tax regimes: Real Profit and Presumed Profit. In 2018, Complementary Law nº155 / 2016 will come into force, amending Complementary Law 123/2006, allowing wineries to opt for the Simple National regime. Currently, wines taxed by Presumed Income or Real Profit have an incidence of 54.73% of charges (ICMS, IPI, PIS, COFINS, CPP ..). One of the taxes responsible for increasing the tax burden is the IPI and its change in the calculation method will increase the tax expense by an average of 50%. In the scenario of legal economy the option for the Simple National will imply in tax planning with significant reduction of costs. In this context, in order to guarantee the competitiveness and sustainability of organizations and, taking into account the need to undertake and innovate, tax management will become necessary in bioindustries.